Pengembangan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Terhadap Hasil Belajar Matematika Siswa Kelas V SDN 101739 Sei Mencirim - Ilham Nazaruddin; Ronald Mahmud S; Ery Novita Sari; Ibnu Hajar Nasution; Umar Said S; Abdul Mukti S (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study discusses the results of research using quasi-experiments (Quasy Experiments) for the Effect of the Teams Games Tournament Type Cooperative Learning Model on Mathematics Learning Outcomes of Class V Students of SDN 101739 Sei Mencirim. The learning outcomes of students in the experimental class using the Teams Games Tournament Type Cooperative Learning Model for the posttest obtained an average value of 80 and a completed KKM value of 15 students with a percentage of 88.23%. There is an influence of the Teams Games Tournament Type Cooperative Learning model on Mathematics learning outcomes of class V students of SDN 101739 Sei Mencirim, this is confirmed by the results of the hypothesis test with a sig value of 0.000.